THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON NEW MEDIA LITERACY ABILITIES OF ENGINEERING PROFILE GYMNASIUM STUDENTS - Peciuliauskiene, Palmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the role of transformational leadership of engineering profile gymnasium (EPG) students on their new media literacy. New media literacy covers a complex of socio-cultural, emotional and technical abilities. The operationalization of the concept of new media literacy in this study is viewed like the interaction of the two continuums: the continuum from consuming media (how to access and understand content) towards producing media (creating and sharing of media content); the continuum from functional to critical media. The study focuses on the collective creation of innovative media, social interaction and transformational leadership of engineering profile gymnasium students. The aim of the article is to explore how engineering profile gymnasium students’ transformational leadership influences to their new media literacy abilities. New media literacy (NML) inventory was used to assess the engineering profile gymnasium students’ new media literacy abilities. Multifactor Leadership Questionnaire (MLQ) was used in the research of leadership expression. The collected data were analysed using path analysis (PA) and confirmatory factor analysis (CFA). The findings confirm that the transformational leadership statistically significantly influences new media literacy abilities: critical consuming, functional prosuming, and critical presuming abilities of engineering profile gymnasium students.